1996
DOI: 10.1177/026010609601100102
|View full text |Cite
|
Sign up to set email alerts
|

Infant Weaning Practices of some TIV Women Resident in Makurdi, Nigeria

Abstract: The weaning practices in infants aged 4 to 9 months of two hundred Tiv mothers in Makurdi, Nigeria were examined. The data was collected using a questionnaire from these randomly selected women from a known population and who regularly visited the public post-natal clinic in Makurdi. The study showed that all the mothers breast-fed their infants and most introduced supplementary feed at 3 to 4 months. Most also fed the traditional pap or "akamu' usually prepared by adding boiling water to fermented maize-sorgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Results from our present study show that about a third of the children examined were malnourished. In other parts of Nigeria different kinds of malnutrition have also been shown, especially among under fives (Igbedioh et al, 1996). Present results are consistent with earlier reports (Cameron and Hofvander, 1983;UNICEF, 1990;Ogbeide, 1992) which suggest that children represent the segment of the population most affected.…”
Section: Discussionsupporting
confidence: 92%
“…Results from our present study show that about a third of the children examined were malnourished. In other parts of Nigeria different kinds of malnutrition have also been shown, especially among under fives (Igbedioh et al, 1996). Present results are consistent with earlier reports (Cameron and Hofvander, 1983;UNICEF, 1990;Ogbeide, 1992) which suggest that children represent the segment of the population most affected.…”
Section: Discussionsupporting
confidence: 92%
“…This same product is often eaten along with meat, stew, vegetable soup, steamed bean cake ('moin-moin') or fried bean cake (Akara) (Igbedioh et al, 1996). The economic strength of the consumers does influence the choice of the supplements (Teniola and Odunfa, 2001).…”
Section: Calderon Et Al (2003)mentioning
confidence: 99%
“…Previous studies in the production of Ogi were on fermentation process (Akinrele, 1970;Banigo et al, 1974;Akingbala et al, 1981;Banigo and Muller, 1972;Sokari, 1992), traditional and modern methods of production of "Ogi , nutritional potentials (Akinrele, 1970;Oke, 1967;Banigo and Muller, 1972b;Akinrele and Bassir, 1967;Akinrele and Edwards, 1971;Fashakin and Ogunsola, 1982), chemical composition of Ogi (Banigo and Muller, 1972;Akinrele, 1970), social status of Ogi (Mensah et al, 1988;Igbedioh et al, 1996) and fortification (Egounlety and Syarief, 1992;Adeniji and Potter, 1978;Akanbi et al, 2003;Adeyemi and Soluade, 1993;Ojofeitimi et al, 1984;Olukoya et al, 1994). The use of high lysine corn for improving the nutritional value of Ogi was reported by Banigo et al (1974) and microbial activities and involvement in the production of Ogi were reported by some researchers (Akingbala et al, 1981;Akoboundu and Hoskins, 1987;Akinrele, 1970;Odunfa and Adeyele, 1985;Olasupo et al, 1997;Teniola and Odunfa, 2002;Ogunbanwo et al, 2003aOgunbanwo et al, , 2003b.…”
Section: Historical Evaluation Of Ogi Productionmentioning
confidence: 99%
“…Infants living in a variety of settings commonly consume inadequate non-breast milk foods or are weaned onto solid foods rather late, with measurable negative impacts on growth and survival. Close observations of the weaning process in modern peasant populations suggest that patterns of weaning are not simply influenced by availability A. STARCHY FOODS taro(l) "cereal" (2) acorn mush (1) yams(l) bread (2) arrowroot flour (1) bananas rice meal (1) bread (1) corn gricldlecake (1) sago briquettes(I) corn mazamorra (1) millet (1) "cake" (1) B. STARCHY SEMI-SOLIDS rice warmed in milk (1) millet gruel (1) maize gruel(l) rye gruel (1) oat soup (1) C. ANIMAL PRODUCTS meat (8) animal milk (11) fish (2) [cow's (5); goat's (5); sheep's (1); reindeer (2)] bone (2) cheese (1), clarified butter/ghee (3) fat (2) meat (4) "soup" (2) broth (1) fat (2) eggs (1) D. NON-STARCHY FRUITS AND VEGETABLES berries (2) "fruit" (1) nuts (1) roots (1) beans (1) E. BEVERAGES coffee (1), tea (1) meat (2) fish (2) seaweed (1) coconut milk (1) pandanus juice (1) water of weaning foods (Almedom and de Waal 1990;el-Bushra et al 1994;Fauveau et al 1992;Igbedioh and Aderiye 1992;Igbedioh et al 1996;Uwaegbute 1991).…”
Section: Other Factors Influencing Weaning Agementioning
confidence: 99%